Use of Reactivated Spent FCC Catalyst as Adsorbent for Lead (II) Ions from Refinery-based Simulated Wastewater - Abdulkareem Abubakar; Ijai Ezekiel Waba; Suleiman Yunusa; Zaharaddeen Sani Gano (Aceh International Journal of Science and Technology, 2021)
Improper handling of wastewater from various industries causes environmental pollution. Hence, this study involved using a reactivated spent FCC catalyst, a cheap and reliable adsorbent for Pb2+ removal from refinery-based simulated wastewater. In contrast, response surface methodology (RSM) was used to determine the optimum operating condition. The adsorptive capacity of the reactivated spent FCC catalyst was observed using different parameters such as temperature, pH, adsorbent dosage, and contact time. At the end of the study, it was found that the optimum condition for removing Pb2+ was at pH of 7, adsorbent dose of 1.75 g, contact time of 75 mins, and temperature of 117 oC. At this condition, the maximum removal efficiency of Pb2+ was found to be 100 %. A quadratic model equation via central composite design under the RSM was developed to predict the Pb2+ removal from all the input parameters. Based on the F-statistic values, the temperature had the greatest influence on the removal of Pb2+ while adsorbent dosage and contact time were also significant.